Nurse Prompting for Prescriber-Led Review of Antimicrobial Use in the Critical Care Unit: A Quality Improvement Intervention with Controlled Interrupted Time Series Analysis. (4th October 2017) - Raybardhan, Sumit; Chung, Bonnie; Ferreira, Danielle; Bitton, Marina; Shin, Phil; Kan, Tiffany; Das, Pavani
Abstract: Background: Audit-and-feedback (A&F) is a core strategy for antimicrobial stewardship programs (ASPs). However, it is resource-intensive, and may not be practical in every setting. Recent guidelines support the non-ASP-led review of antimicrobials by prescribers (AM-REV) on a routine basis. A sustainable strategy for AM-REV in a critical care unit (CrCU) may improve antimicrobial utilization without additional ASP resources. Methods: Using a quality improvement framework, a prompt for AM-REV strategy was created. The primary outcome was antimicrobial utilization defined by days of therapy/1000 patient-days (AM-DOT). A secondary process outcome was the proportion of relevant cases for which an antimicrobial prompt was provided to the prescriber (AM-PRT). Balancing measures included CrCU mortality rates, length of stay, and 48-hours re-admission rates. Utilization data of a control class of medications (proton-pump inhibitors) was also collected. AM-DOT was collected for 34 months pre- and 14 months post-intervention. AM-PRT was collected for 3 months pre- and 12 months post-intervention. Segmented regression analysis was used for the primary outcome, with a descriptive analysis of secondary outcomes. Results: CrCU nurses were recruited to prompt AM-REV during CrCU rounds. A standardized script was developed to insert day of antimicrobial therapy into rounds; prescribers were primed to respond with affirmation, rationale, and clinical decisions. Plan-Do-Study-Act (PDSA) cycles further refined the intervention to include nursing reminders from CrCU pharmacists and increased engagement of nurses during formal A&F rounds. Prior to the intervention, monthly AM-DOT was 804 with a positive trend (7.3 DOT/1000PD, P < 0.05). Post-intervention resulted in an immediate reduction of 217 DOT/1000 PD ( P < 0.05) with a non-significant negative AM-DOT trend, representing a 20% (95% CI –15%, -25%) reduction in AM-DOT per month. There was no significant change in utilization of the control class of medications. The ABX-PRT increased from 17% to 50% during the intervention period. Balancing measures were comparable pre and post-intervention. Conclusion: Nurse prompting of AM-REV can lead to significant reductions in antimicrobial utilization, providing a non-ASP mechanism of sustaining antimicrobial awareness. Disclosures: All authors: No reported disclosures.